Pregnancy urine biomarkers for effectively preeclampsia prediction: a systematic review and meta-analysis - Juanhong Wu; Yingsha Yao; Ting Wang; Ting Xu; Ruoan Jiang (Hypertension in Pregnancy)
Preeclampsia (PE) is a common multi-organ disorder in pregnancy. Urine as a source for test samples is noninvasive and easy to obtain. This study followed the Priority Reporting Project for Systematic Evaluation and Meta-Analysis protocol. We searched PubMed and Web of Science databases for studies relating to urine biomarker analysis for PE from inception to the 28th of February 2023. The Chi-squared test was utilized to evaluate the statistical heterogeneity of the results. The combined sensitivity, combined specificity, combined positive likelihood ratio, combined negative likelihood ratio, combined diagnostic odds ratio for urine analysis in the context of PE were calculated. Sixty-five studies were eventually included in the final analysis. In only hypertensive disorders of pregnancy (HDP) pregnant women, the the area under the summary receiver operating characteristic curve (AUC) of urine analysis to predict PE was 0.93 (0.91–0.95). The results show that spot random urine analysis or shortened-hour urinary analysis for the diagnosis of PE is a credible alternative method when 24-h urine collection is difficult to complete. The protein/creatinine ratio from spot random urine analysis may be an effective biomarker of the further progression of HDP into PE.